Morpho-Physiological Responses of Shade-Loving Fern Polystichum spp. to Single and Combined Lead and Light Stress - Anna Pietrak; Łukasz Łopusiewicz; Małgorzata Gałczyńska; Piotr Salachna (Agronomy)
The effects of lead (Pb) stress on plant growth and physiological processes may depend on other environmental stresses coinciding. Knowledge of the response of shade-loving plants to stresses, particularly the relationship between Pb stress and light stress, is lacking. The effects of single and combined Pb and light stress on the growth and physiological parameters of Polystichum setiferum and Polystichum setiferum ‘Proliferum’ ferns were evaluated under glasshouse conditions. Treatments comprised control (80% shade, ~111 μmol m−2 s−1 photosynthetic photon flux density, PPFD), light stress (100% full sunlight, ~525 μmol m−2 s−1 PPFD), 1000 mg dm−3 Pb solution applied to plants under shade and light stress conditions. Under full sunlight, plants had damaged leaves and reduced leaf biomass, and underground parts of the plants had levels of photosynthetic pigments, reducing sugars and total flavonoids. The Pb stress decreased plant growth, reducing sugars, and free amino acids content, and at the same time increased chlorophyll content in P. setiferum and total polyphenols and flavonoid content in P. setiferum ‘Proliferum’. The combined stress of Pb and full sunlight reduced plant growth and the accumulation of pigments, reducing sugars, and free amino acids without affecting the levels of secondary metabolites. P. setiferum plants accumulated more Pb than P. setiferum ‘Proliferum.’ The fern P. setiferum ‘Proliferum’ was more tolerant to abiotic stresses than the fern P. setiferum. This study provided new insights into the response of shade-loving ornamental plants to single and combined Pb and light stress.